Association between socioeconomic status and severity of oral epithelial dysplasia using a Taiwanese Nationwide Oral Mucosal Screening Program: a retrospective analysis - Tien-En Chiang; Yu-Chun Lin; Chi-Tsung Wu; Sheng-Tang Wu; Yuan-Wu Chen (BMC, 2022)
Abstract Background The study aimed to investigate the association between socioeconomic status and severity of oral epithelial dysplasia (OED) using current data from the Taiwanese Nationwide Oral Mucosal Screening Program (TNOMSP). Methods This retrospective analysis was conducted in the Department of Oral and Maxillofacial Surgery at a general hospital in Taipei, Taiwan. A total of 134 participants were analysed from a previous study database of 150 patients. The inclusion criteria included age > 20 years and a history of either tobacco or betel nut use. Background information, including para-habits such as betel and tobacco use, was analysed using the Pearson chi-square (χ2) test; furthermore, the correlation of background information with OED severity was investigated using logistic regression (mild or moderate/severe). Results High school education level (P < 0.001), poor self-awareness (P = 0.002), current betel use (P < 0.001), and tobacco use (P = 0.003) were highly correlated with moderate- and severe OED (P < 0.05). The odds ratio (OR) of education status above senior high school was 0.03 (95% confidence interval [CI] 0.01-0.15, P < 0.001), while that of junior high school was 1. Current betel chewing (OR 6.57 [95% CI 1.17-37.0], P = 0.033) was significantly associated with OED severity compared with never or ex-use of betel. Conclusions We found a strong correlation between the severity of OED and current betel use and low education status. The current study revealed that the socioeconomic status, poor self-awareness, and para-habit history of the patients with OED should be evaluated to identify high-risk individuals using TNOMSP.